Analisis Komparatif Teori-Teori Belajar dalam Konteks Pendidikan Abad 21 - Rizqan Fadhli; Thiara Deah Lestari; Melisa Putri Dwi Ningrum; Asiyah Asiyah (Pusat Riset dan Inovasi Nasional, 2026)
Teachers must put in a lot of time and energy into their lessons if they want their pupils to study at their own pace and level. The study's overarching goal is to dissect the learning process from the perspectives of three prominent theoretical frameworks behaviorist, cognitive, and constructivist and to draw conclusions about the attributes, responsibilities, and applicability of these frameworks to various learning activities based on students' developmental stages. The approach to writing is rooted on the methodology of literature review. Books, online books, theses, journals, online journals, scientific articles, periodicals, news, and other sources are all part of the accessible theories technique. The study's findings support behaviorist theory's claims that students' actions may be influenced and their abilities enhanced via the use of routine, practice, and reinforcement based on rewards and punishments, particularly during certain phases of development. To promote deeper comprehension, cognitive theory places an emphasis on pupils' intrinsic thought processes and on learning that is age-appropriate. Meanwhile, in constructivist theory, the role of the instructor is that of a facilitator, and the students are seen as the primary agents of change in the learning process.